Greenhouse gas implications of novel and conventional rice production technologies in the Eastern-Gangetic plains - Alam, K.; Biswas, Wahidul; Bell, R. (Elsevier science, 2015)
Wetland rice (Oryza sativa L.) production contributes 55% of agricultural greenhouse gas (GHG) emissions in the world. Hence any new technology with the potential to reduce the GHG emissions of wetland rice could make a significant contribution to total global warming mitigation by agriculture. We applied a streamlined life cycle assessment to the effect of a novel unpuddled transplanting of rice and of increased crop residue retention on GHG emissions from rice fields in the Eastern Gangetic Plains. We compared them with the conventional puddling of soils and current residue retention for transplanting. The GHG emissions from one tonne of rice production for the following four cropping practices were studied: a) conventional puddled transplanting with low residue retention (CTLR); b) conventional puddled transplanting with high residue retention (CTHR); c) unpuddled transplanting following strip tillage with low residue retention (UTLR) and; d) unpuddled transplanting with high residue retention (UTHR). The emissions recorded on-farm and emissions related to pre-farm activities were converted to CO2-eq using Global Warming Potential (GWP) values of GHGs for 20-, 100- and 500-year time horizons. The GHG emissions of 1 tonne of rice varied from 1.11 to 1.57 tonne CO2-eq in the 100-year horizon. For all four treatments, soil methane (CH4) was the predominant GHG emitted (comprising 60–67% of the total) followed by emission from on-farm machinery use. The UTLR was the most effective GHG mitigation option (it avoided 29%, 16% and 6% of the total GHG emissions in comparison with CTHR, CTLR and UTHR, respectively) in wetland rice production. The novel minimum tillage establishment approach for rice involving strip tillage followed by UT has potential to increase global warming mitigation of wetland rice in the Eastern Gangetic Plains, but further research is needed to assess the role of increased residue retention.